Review paperSacroiliac joint pain as an important element of psoriatic arthritis diagnosis - Krawczyk-Wasielewska, Agnieszka; Skorupska, Elżbieta; Samborski, Włodzimierz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Psoriatic arthritis (PsA) is a chronic inflammatory disease characterized by the coexistence of arthritis with psoriasis of the skin and nails. The sacroiliac joints were observed in 34-78% of patients with psoriatic arthritis. Due to such a high prevalence of SIJ dysfunction, understanding pathophysiology of pain and the associated pain pattern becomes a very important aspect of PsA diagnosis. As far as the etiology of SI joint dysfunction is concerned, it has not been disambiguated yet. Among the main causative factors, injuries and strains of the structures surrounding the joint are noted. Joint pathology usually manifests itself by pain occurring within the area of the joint. The causes of pain may be divided into two categories: intra-articular and extra-articular. Pain caused by the SI joint may be nociceptive or neural in nature, whereas the pain pattern characteristic of the joint correlates with its innervation and is consistent with S2 dorsal rami.